'He shall have care of the garden, its cultivation and produce': Workhouse Gardens and Gardening, c.1780‐1835. (10th August 2020) - Collinge, Peter
Abstract: Where productive workhouse gardens and land existed they comprised an essential aspect of institutional management, yet they feature only briefly in accounts of workhouses and inmates' lives. Their location, desirability and benefits, however, occupied the minds of parish officials, doctors, Enlightenment thinkers and pamphleteers. Workhouse gardens provided food and were regarded as mechanisms for discipline, moral encouragement and therapeutic benefit, and they illustrate the management of pauperism in local contexts. Eliciting a greater understanding of their significance and refining established assumptions about dietary provision for inmates, this article analyses itemised bills, nurserymen's ledgers and attitudes surrounding workhouse gardens and workhouse land.